Pelatihan Life Skill Membuat Sablon dalam Meningkatkan Kemandirian Warga Belajar di Sanggar Kegiatan Belajar Kabupaten Ciamis: Studi terhadap Warga Belajar di Sanggar Kegiatan Belajar Kabupaten Ciamis - Dhanni Meisya; Lilis Karwati (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2023)
This research has a background problem, namely the lack of skills in the community, the large number of unemployed in Indonesia, and the large number of requests from the public to hold life skills training. The purpose of this study is to find out the process and results of screen printing training by residents studying at the Ciamis Regency SKB. The method used in this study is a qualitative descriptive method with data collection techniques namely interviews, observation, and documentation. Data analysis techniques, namely data reduction, data presentation, and data verification and drawing conclusions. The data sources in this study are primary data sources and secondary data sources. The research results obtained in the life skill training process research to make screen printing in increasing the independence of citizens learning at the Ciamis Learning Activity Center (SKB), namely screen printing training has infrastructure such as classrooms, tools and materials for screen printing. In carrying out tutoring, namely providing material and practical methods so that learning residents can easily understand. The purpose of the screen printing training program is to increase and develop the life skills of learning citizens through screen printing training so that they have independence in their lives and have skills for their lives in the future. The results of the life skills training in making screen printing, residents learn to gain knowledge about how to make screen printing and have skills in making screen printing and learning residents can also open businesses or get better jobs. In conclusion, after participating in training activities, learning residents can get a job or can adjust to a better job and can open a business in the field of screen printing. Obtain sufficient income, have self-actualization and develop skills for a better life. Conculusions can improve the life skills and independence of learning citizens